Comparação entre as metodologias tradicionais de inspeção e a metodologia de inspeção baseada em risco aplicadas a vasos de topo de destilações - Monteiro, Vinicius Holanda (Brasil, 2021)
In a market where the optimization of resources is increasingly sought, often scarce, the RBI methodology presents itself as a viable option for improvement in this regard when referring to the equipment inspection sector. The objective of this work is to present a comparison between the RBI methodology and the traditional inspection methodologies, with a focus on resource optimization in the inspection and maintenance of pressure vessels of the overhead system of atmospheric and vacuum crude units. For this, we briefly explore the concepts of these inspection methodologies, seeking to highlight their main differences. From this, for the evaluation of traditional methodologies, we list three overhead vessels and present the inspection plan and the scope of the existing inspection services for these equipments. Then, we apply the risk-based inspection methodology and define the same elements mentioned. Finally, we compare the inspection intervals and the scope of inspection services defined for each methodology. The methodology used respects the characteristics of quantitative, applied, exploratory, bibliographic and documentary research. The results showed that the desired optimization was not possible in relation to the inspection intervals, due to legal requirements. On the other hand, it was possible in relation to the scope of inspection services, which are considerably reduced and distributed in order to dedicate the greatest efforts to the equipment with the greatest risks.